Behavioral Responses of Chrysoperla defreitasi (Neuroptera: Chrysopidae) and Myzus persicae (Hemiptera: Aphididae) to Volatile Compounds from Wild and Domesticated Ugni molinae - Manuel Chacón-Fuentes; Leonardo Bardehle; César Burgos-Díaz; Marcelo Lizama; Daniel Martínez-Cisterna; Mauricio Opazo-Navarrete; Cristina Bravo-Reyes; Andrés Quiroz (Insects, 2025)
Domestication significantly altered the phenotypic and chemical traits of murtilla, notably reducing the emission of volatile compounds essential for plant–insect interactions. This reduction may affect the plant’s natural defense mechanisms, influencing its interactions with herbivores and predators. Therefore, this study tests whether domestication reduces volatile emissions in murtilla, increasing aphid preference and decreasing lacewing attraction. We selected wild ancestors (19-1, 22-1, and 23-2) from a longterm Ugni molinae germplasm bank. Crosses between these wild ancestors generated four first-generation domesticated ecotypes, 10-1, 16-16, 17-4, and 66-2, used in this study. These first-generation domesticated ecotypes were six years old at the time of the study and were used for comparisons in volatile profile and insect interaction analyses. The olfactometric preference index (OPI) for lacewing larvae and aphids revealed that wild ancestors attracted more predators than domesticated plants. For example, Ecotype 19-1 had an OPI of 1.64 for larvae and 1.49 for aphids, while Ecotype 10-1 showed lower attraction (OPI of 1.01 for larvae and 1.00 for aphids). Gas chromatography analysis identified differences in volatile organic compounds, with wild ancestor ecotypes emitting higher levels of compounds such as 2-hexanone, 1,8-cineole, and α-caryophyllene. Principal component analysis and hierarchical clustering confirmed these chemical distinctions. In olfactometer assays, lacewing larvae preferred α-caryophyllene and 2,4-dimethyl acetophenone, while aphids favored 2-hexanone and 3-hexanol. In Y-tube assays, lacewing adults showed strong attraction to α-pinene and 2,4-dimethyl acetophenone, with preferences increasing with concentration. These results indicate that domestication altered the volatile murtilla profile, reducing its attractiveness to natural predators while increasing its susceptibility to herbivores, supporting the plant domestication defense theory.